Pengaruh Pelatihan Motivasi Kerja terhadap Kinerja Perawat Pelaksana dalam Memberikan Asuhan Keperawatan di RS Husada Jakarta - Saragih, Dameria (Jurnal Kesehatan Holistic, 2021)
Nursing service which is one of the duties and responsibilities of nurses is to provide nursing care. The purpose of this study was to analyze the effect of work motivation training on the performance of nurses and to analyze the effect of individual characteristics on the performance of nurses at Husada Hospital, Jakarta. Quasi Experimental research design with Pre-Post Test Group Design. Respondents in the intervention group were 27 respondents who were selected by purposive sampling technique. Respondents in the control group were 27 people. Respondents in the intervention group were given motivation training as well as supervision and observation for 4 weeks. Collecting data using questionnaires and work performance appraisal observation sheets then analyzed bivariate with paired sample t-test and multivariate test with ancova test. The results showed that there is an influence among performance with motivation training and counfonding variables, the result is Corrected Model 0.000. Meanwhile, partially, the work duration is 0.000 and motivation training is 0.009. Motivation training and length of work affect work performance as much as 46.6%. Researchers recommend motivational training in improving work performance in providing nursing care.